2018
DOI: 10.3390/w10101400
|View full text |Cite
|
Sign up to set email alerts
|

Failure and Collapse of Ancient Agricultural Stone Terraces: On-Site Effects on Soil and Vegetation

Abstract: Ancient agricultural stone terraces, dated to the Roman and Byzantine ages, are prevalent across the Negev drylands of Southern Israel. The goal of these structures was to reduce hydrological connectivity by harvesting water runoff and controlling soil erosion, thus allowing cultivation of cereals. Land abandonment and the lack of maintenance have led to the failure and collapse of many of these stone terraces. The objective of this study was to assess the effect of failure and collapse of terraces on the on-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Abandonment of terrace landscape can have serious implications on the environment and cause structural damages, when triggered by severe rainfall, as happened in the case of Liguria region (Italy) in 2014 [42]. Studies have shown that soil erosion and land degradation process is accelerated in terraces that lack maintenance and vegetation cover, compared to well-maintained ones with crop cultivation or dense wild vegetation [43][44][45]. Dry stone walls are paramount to reduce slope length, trap erosion sendiments and reduce soil run-off.…”
Section: Discussionmentioning
confidence: 99%
“…Abandonment of terrace landscape can have serious implications on the environment and cause structural damages, when triggered by severe rainfall, as happened in the case of Liguria region (Italy) in 2014 [42]. Studies have shown that soil erosion and land degradation process is accelerated in terraces that lack maintenance and vegetation cover, compared to well-maintained ones with crop cultivation or dense wild vegetation [43][44][45]. Dry stone walls are paramount to reduce slope length, trap erosion sendiments and reduce soil run-off.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, as the hill slope becomes steeper, the terrace becomes narrower, and the height of the terrace wall increases. A taller terrace wall has a greater chance of collapse and requires more maintenance, which is more difficult where the terrace is narrow [68]. In addition, a narrow terrace prevents the use of machinery or animal power and farmers have to use locally made hand-held agricultural tools appropriate to the narrow terraces, which sometimes are as narrow as 1 m wide.…”
Section: Discussionmentioning
confidence: 99%
“…The simple terraces revealed in this study are structurally different from those that are prevalent across the northern and central Negev region. These terraces, characterized by multilayer staircase-shaped constructions that strengthen the structure and allow excess water to gradually cascade down (Stavi et al, 2018b, 2019), have been predominantly dated to the Byzantine and Early Islamic periods (e.g. Ashkenazi, 2007, 2013; Avni et al, 2013; Bruins, 2012; Evenari et al, 1971; Haiman, 2012; Haiman et al, 2020).…”
Section: Methodsmentioning
confidence: 99%